The Effect of Intravenous Metoclopramide on Gastric Emptying of Opium-dependent Patients based on Ultrasonographic Criteria; a Case-control Study - Mosaffa, Faramarz; Arhami Dolatabadi, Ali; Raoufi, Masoomeh; Golpour, Faezeh; Ghasemi, Mahshid; Yazdipoor, Mohammad Javad; Memary, Elham (Archives of Academic Emergency Medicine, 2023)
Introduction: Induction of anesthesia for emergency procedures, without prior gastric preparation and incomplete fasting, is associated with the risk of reflux of stomach contents and aspiration. This study aimed to evaluate the effect of intravenous (IV) metoclopramide administration on gastric emptying in opium users, candidate for procedural sedation and analgesia (PSA). Methods: In the present case-control study, opium-dependent (case) and non-dependent (control) patients in need of PSA were administered with 10 mg IV metoclopramide after undergoing gastric ultrasonography for determination of its area and contents. Then, 30 minutes after the administration of metoclopramide, the area and contents of the stomach were measured again and compared with the measures obtained before the intervention. Results: 135 patients were evaluated in three groups of 45, including the case, control, and placebo groups. The three groups were similar regarding mean age (p = 0.068), sex (p = 0.067), weight (p = 0.596), height (p = 0.671), body mass index (BMI) (p = 0.877), duration of fasting (p = 0.596), and type of gastric contents (p = 0.124). Mean antral cross-sectional area (CSA) of the study participants in the case, control, and placebo groups before the administration of the drug was 8.49 ± 1.40, 8.31 ± 2.56, and 6.56 ± 1.72 cm2, respectively. Mean gastric area in the case (p < 0.001) and control (p < 0.001) groups had significantly decreased after the intervention. Mean antral gastric grade of gastric contents in the case (p < 0.001) and control (p < 0.001) groups had significantly decreased after the intervention. Conclusion: It seems that metoclopramide administration in opium users in need of PSA leads to a significant decrease in mean gastric area and increases gastric emptying.